Penerapan Diferensiasi Proses dalam PjBL untuk Mengoptimalkan Minat dan Potensi Siswa Kelas XI: Penelitian - Restin Saputri Ue Raja; Wida Rahayuningtyas (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The role of teachers as facilitators in 21st century education is to provide a learning process that accommodates all the needs of students such as interests, potential, learning styles, student characteristics, and the strengths and weaknesses of students. Learning theater performance material in arts and culture subjects can be packaged into interesting projects to provide meaningful experiences and develop students' knowledge and skills. Therefore, teachers need to design learning that is centered on students' interests and potential by giving students assignments to work on projects according to their abilities. This study contains various learning steps with a differentiation approach and aims to determine the effectiveness of the integration of differentiation learning carried out in class XI F of SMA Negeri 10 Malang. The activities that have occurred and in-depth analysis to determine the effectiveness of learning and its relationship to student interests are carried out using the descriptive qualitative analysis method. The research conducted found that the integration of differentiation learning has a good impact on the learning process and accommodates students' interests and potential as a whole.